Analisis Konseptual Customer Relationship Management (CRM) dalam Meningkatkan Kepuasan Nasabah Bank Jatim KC Bangkalan - Putriana; Siti Alfiyah (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
In the increasingly tight banking business competition, the main strategy to increase customer satisfaction and loyalty is Customer Relationship Management (CRM). This study collected data from bank management, employees, and customers through a descriptive qualitative approach with in-depth interviews, observations, and documentation. The results show that the CRM strategy used by Bank Jatim KC Bangkalan, such as the use of technology, better communication, and improving customer satisfaction, However, customer data management, human resource readiness, and technology optimization are the main problems in CRM implementation. To overcome this problem, it is recommended to improve the data management system, optimize AI-based technology, provide employee training, and regularly evaluate CRM programs. In the digital era, CRM can be an important component in increasing bank competitiveness with the right strategy.